Time preferences and political regimes: Evidence from reunified Germany - Markus Pannenberg; Tim Friehe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper presents evidence on the impact of political regimes on time preferences using survey measures of present bias and patience. Treating the German separation and reunification as a natural experiment, our results indicate that the GDR's socialist regime significantly diminished the present bias of its former citizens, while their patience appears to be unaffected.
Keywords: D02; D12; 330